2022
DOI: 10.3390/diagnostics12123176
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Prostate Cancer Diagnostics with 18F-PSMA-1007 PET/CT: A Systematic Review of the Current State

Abstract: Background: Early diagnosis recurrent prostate cancer is a cornerstone for further adequate therapy planning. Therefore, clinical practice and research still focuses on diagnostic tools that can detect prostate cancer in early recurrence when it is undetectable in conventional diagnostic imaging. 18F-PSMA-1007 PET/CT is a novel method to evaluate patients with biochemical recurrent PCa. The aim of this review was to evaluate the role of 18F-PSMA-1007 PET/CT in prostate cancer local recurrence, lymph node metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Different PSMA radiotracers have been reported to present distinctive pharmacokinetic patterns, which might result in different parametric imaging.For instance, although PSMA-11 showed faster intratumoral uptake than PSMA-617 and PSMA-1007, studies using these 68 Ga/ 18 F labeled PSMA-targeted tracers still adopted a mean time interval between tracer injection and imaging acquisition between 50 and 120 min. 1,[29][30][31] Recently, Liu et al suggested that 68 Ga-PSMA-11 PET scanned 35-59 min p.i. showed a similar tumor uptake but lower urinary bladder activity interference.…”
Section: Discussionmentioning
confidence: 99%
“…Different PSMA radiotracers have been reported to present distinctive pharmacokinetic patterns, which might result in different parametric imaging.For instance, although PSMA-11 showed faster intratumoral uptake than PSMA-617 and PSMA-1007, studies using these 68 Ga/ 18 F labeled PSMA-targeted tracers still adopted a mean time interval between tracer injection and imaging acquisition between 50 and 120 min. 1,[29][30][31] Recently, Liu et al suggested that 68 Ga-PSMA-11 PET scanned 35-59 min p.i. showed a similar tumor uptake but lower urinary bladder activity interference.…”
Section: Discussionmentioning
confidence: 99%
“…Additional investigation with large cohorts must be conducted to demonstrate if [ 18 F]PSMA-1007 can be used as a theranostics pair for PSMA-617 instead of [ 68 Ga]Ga-PSMA-11 in the future [85,87,90,92]. Despite having several advantages over [ 68 Ga]Ga-PSMA-11, [ 18 F]PSMA-1007 also has a major drawback as occasional unspecific bone uptake [57,93].…”
Section: Application Of Radiomics and Ai In [ 18 F]psma Pet/ct Image-...mentioning
confidence: 99%
“…Historically, PET has relied heavily on several generalized radiotracers that exploit the increased metabolic activity of tumors. A radiolabeled glucose derivative, (18)F-2-deoxy-2-fluoro-D: -glucose (FDG)( 18 F-FDG), is a common radiotracer used for many malignancies; however, it lacks sensitivity and specificity for PC [84].…”
Section: Diagnosticsmentioning
confidence: 99%